THE CONCEPT OF HUMAN BEING, LIFE AND DEATH IN THE POETRY OF OMER TARIN AND RAHMAN BABA (A COMPARATIVE STUDY) - Wisal Ahmad Khan; Dr. Sania Gul; Sobia Siraj (International Journal of Contemporary Issues in Social Sciences, 2023)
In this research study, a comparative analysis of selected poems by Omer Tarin, a prominent Pakistani mystic poet who wrote in English, and Rahman Baba, a renowned Pakistani mystic poet who wrote in Pashto, will be conducted within the context of mysticism. During the course of this research, I randomly selected poems from two books: ’A Sad Piper’ and ’Burnt Offering,’ published in 1994 and 1996, respectively, authored by Omer Tarin. Additionally, some poems were chosen from the poetry of Rahman Baba, as translated by Robort Sampson Momin Khan in 2005. These selected poems will be examined in the context of mysticism, utilizing the Reader Response Theory technique. The focus of the analysis will be on identifying common mystical elements and themes shared by the two poets. This investigation aims to determine how they perceive various aspects such as the human condition, human life, death, and the quest for the Ultimate Truth. Furthermore, an exploration will be made into whether Omer Tarin, as a modern poet, exhibits any influence from the works of the older poet Rahman Baba.